The homozygosity confirmation for multiplied haploid Japanese fumble, Paralichthys olivaceus, by microsatellite DNA markers - Yang Lee; X .Yongxin; Singh Paul (Advances in Aquaculture and Fisheries Management, 2019)
A total of 845 doubled haploids Japanese flounder, Paralichthys olivaceus from three spawns were produced by utilizing hydrostatic pressure treatments on eggs fertilized with ultraviolet (UV)-irradiated sperm of red sea bream (Pagrus major). 481 polymorphic microsatellite markers were used to identify the homozygosity of these doubled haploids, of which, only 31% (265 out of 845) individuals were fully homozygous at all loci tested, while, the rest 580 offspring were homozygous at 183 to 320 loci. Additionally, the embryonic development and external morphology of doubled haploids were also observed and recorded. The whole process of embryonic development was divided into 19 stages based on the morphological characteristics of the developing embryo. Hatching took place 73 to 74 h after fertilization. The means of body weight, body length and body depth in 360 days old fishes were always small in doubled haploids and large in normal diploids, but, the standard deviations and coefficients of variation of doubled haploids were significantly higher than those of normal diploids